One Dimensional Steady Flow Analysis Using HECRAS – A case of River Jhelum, Jammu and Kashmir - Ahmad, Hakim Farooq; Alam, Akhtar; Bhat, M. Sultan; Ahmad, Shabir (European Scientific Journal, ESJ, 2016)
Floods have been recurrent phenomena in the study area. A heavy precipitation, usually coming during the end months of the summer season in association with sudden cloudburst, leads to severe flooding in the study area. By now the catchment area of the river is already saturated and the high run-off swells the rivers beyond their capacity. The present study describes the application of HEC RAS Model for flood studies in the river Jhelum Kashmir valley. The peak flood records were used as inputs into HEC RAS model to find out the resultant expected flood levels. The resultant output generated by the model shows an overflow at maximum locations of the river under study for 50 years and above return period. This purpose is to give a hand to policy makers, planners and insurers, to develop a robust strategy for the development of flood mitigation measures and plans to minimise the losses associated with the disaster in the study area.